HUBUNGAN MOTIVASI DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR MUPEL PJOK (Universitas Negeri Semarang, 2020)
The purpose of this study was to examine the existence of a positive and significant correlation between motivation and learning discipline towards outcomes of sport and physical learning to the fifth grade students of the Larasati Elementary School Cluster, Gunungpati, Semarang. This research was a quantitative approach. The sampling technique used saturated sampling of 119 students. The data collection techniques were questionnaires, observation, interviews, and documentation. The instrument test used validity and reliability test. The data analysis techniques used were descriptive statistical analysis and product moment correlation analysis. The results of data analysis in this study showed that there was a positive and significant correlations between motivation and learning discipline and sport science learning outcomes, Rcount =0.743, andÂ included in a strong category and contributes 55,1%. The conclusion of this study there was a positive and significant correlation between motivation and learning discipline towards outcomes of sport and physical learning at fifth grade students of the Larasati Elementary School Cluster, Gunungpati, Semarang.